2011
DOI: 10.1123/jsr.20.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Isokinetic Assessment of Shoulder-Rotator Strength: A Systematic Review of the Effect of Position

Abstract: Context: Isokinetic assessment of shoulder internal-(IR) and external-rotator (ER) strength is commonly used with many different postures (sitting, standing, or supine) and shoulder positions (frontal or scapular plane with 45° or 90° of ab duction). Objective: To conduct a systematic review to determine the influence of position on the intersession reliability of the assessment of IR and ER isokinetic strength, to identify the most reliable position, and to de termine which isokinetic variable appears to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 39 publications
2
67
0
1
Order By: Relevance
“…This position seemed the most reliable for IR strength assessment, since its reliability has been studied in most methodologically high-quality studies ( The mentioned position has many advantages because is more comfortable, physiological and safe. More, it elicits optimal torque; and it showed good to excellent reliability for concentric/eccentric shoulder internal rotation strength (Davies, 1992;Edouard et al, 2011).…”
Section: Discussion:-mentioning
confidence: 99%
“…This position seemed the most reliable for IR strength assessment, since its reliability has been studied in most methodologically high-quality studies ( The mentioned position has many advantages because is more comfortable, physiological and safe. More, it elicits optimal torque; and it showed good to excellent reliability for concentric/eccentric shoulder internal rotation strength (Davies, 1992;Edouard et al, 2011).…”
Section: Discussion:-mentioning
confidence: 99%
“…Testretest intraclass correlation coefficients (ICCs) exceed 0.9 in the case of the assessments of knee extensor and flexor torque [30], shoulder rotator torque [11,12,31], and the height of the centre of gravity after the CMJ [22,23]. The test-retest which was performed before the first measurement in the current study confirmed these results, since the ICC values ranged from 0.91 (for the external rotators at a velocity of 60 deg/s) to 0.98 (for jump height).…”
Section: Pol J Sport Tourism 2017 24 221-227mentioning
confidence: 99%
“…The subjects were tested in a sitting position with 45° of shoulder abduction in the scapular plane [11,12]. The range of motion (ROM) was 70°.…”
Section: Pol J Sport Tourism 2017 24 221-227mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, objective assessment of muscle strength in all athletes is crucial to the sportive success of athletes and prevention of injuries. Despite several studies in the literature exploring the upper extremity isokinetic strength profile in various sports fields such as swimming, handball, volleyball, tennis, water polo, cricket, judo, and basketball (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), no study has examined the upper extremity isokinetic muscle strength characteristic in weightlifters.…”
Section: Introductionmentioning
confidence: 99%